Faktor Yang Berhubungan Dengan Kepatuhan Penggunaan APD Pada Perawat Diruang Rawat Inap RSD Konawe Selatan - Vivilahi Ribut Mekarsuci; Fifi Nirmala G; Indah Ade Prianti (Lembaga Pengembangan Kinerja Dosen, 2024)
Nurses have a large risk of transmitting infections to patients when carrying out nursing procedures/care. This is because nurses are in direct contact with patients for approximately 24 hours to provide nursing care. The aim of this research is to determine the factors related to compliance with the use of PPE among nurses in the inpatient wards at RSD Konawe Selatan. The type of research used is analytical observation using cross sectional research techniques. The results of the analysis show that there is a relationship between knowledge (P = 0.054), attitude (P = 0.099), action (P = 0.014), and supervision (P = 0.003) with compliance with the use of PPE. Then the results of the analysis also showed that there was no relationship between the availability of PPE (P=0.749) and compliance with PPE use. Conclusion: There is a relationship between knowledge, attitudes, actions and supervision and compliance with the use of PPE among nurses at RSD Konsel. Then there is no relationship between the availability of PPE and compliance with PPE use at Konsel RSD. It is hoped that RSD Konsel can provide outreach or education about PPE, provide PPE that is comfortable to use, and supervise or monitor nurses.